Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 155183 by mathdanisur last updated on 26/Sep/21

Answered by aleks041103 last updated on 26/Sep/21

1−tan^2 (x/2^k )=((cos^2 (x/2^k )−sin^2 (x/2^k ))/(cos^2 (x/2^k )))=((cos(x/2^(k−1) ))/(cos^2 (x/2^k )))  Π_(k=1) ^n cos(x/2^(k−1) )=cosx cos(x/2) ... cos(x/2^(n−1) )=  =(1/(sin(x/2^(n−1) )))sin(x/2^(n−1) )cos(x/2^(n−1) )cos(x/2^(n−2) )...cos(x/2)cosx=  =(1/(sin(x/2^(n−1) ))) (1/2)sin(x/2^(n−2) )cos(x/2^(n−2) )...cos(x/2)cosx=  =(1/(2^2 sin(x/2^(n−1) )))sin(x/2^(n−3) )Π_(k=0) ^(n−3) cos(x/2^k )=...=  =(1/(2^m sin(x/2^(n−1) )))sin(x/2^(n−1−m) )Π_(k=0) ^(n−1−m) cos(x/2^k )=  =(1/(2^(n−1) sin(x/2^(n−1) )))sinxcosx=((sin(2x))/(2^n sin((x/2^(n−1) ))))  Π_(k=1) ^n cos(x/2^k )=Π_(k=1) ^n cos((x/2)/2^(k−1) )=  =((sin(2(x/2)))/(2^n sin(((x/2)/2^(n−1) ))))=((sinx)/(2^n sin(x/2^n )))  ⇒Π_(k=1) ^n ((cos(x/2^(k−1) ))/(cos^2 (x/2^k )))=(((Π_(k=1) ^n cos(x/2^(k−1) )))/((Π_(k=1) ^n cos(x/2^k ))^2 ))=  =(((sin(2x))/(2^n sin((x/2^(n−1) ))))/((((sinx)/(2^n sin(x/2^n ))))^2 ))=((sin(2x)2^(2n) sin^2 (x/2^n ))/(2^n sin((2x)/2^n )sin^2 x))=  =((2sinx cosx 2^n  sin^2 (x/2^n ))/(2sin(x/2^n )cos(x/2^n )sin^2 x))=((2^n cosx sin(x/2^n ))/(cos(x/2^n )sinx))=  =2^n ((tan((x/2^n )))/(tan(x)))  ⇒Ω=lim_(x→0)  (x/(tan(x)))lim_(n→∞) ((tan(x/2^n ))/(x/2^n ))=1

1tan2x2k=cos2x2ksin2x2kcos2x2k=cosx2k1cos2x2knk=1cosx2k1=cosxcosx2...cosx2n1==1sinx2n1sinx2n1cosx2n1cosx2n2...cosx2cosx==1sinx2n112sinx2n2cosx2n2...cosx2cosx==122sinx2n1sinx2n3n3k=0cosx2k=...==12msinx2n1sinx2n1mn1mk=0cosx2k==12n1sinx2n1sinxcosx=sin(2x)2nsin(x2n1)nk=1cosx2k=nk=1cosx/22k1==sin(2(x/2))2nsin(x/22n1)=sinx2nsinx2nnk=1cosx2k1cos2x2k=(nk=1cosx2k1)(nk=1cosx2k)2==sin(2x)2nsin(x2n1)(sinx2nsinx2n)2=sin(2x)22nsin2x2n2nsin2x2nsin2x==2sinxcosx2nsin2x2n2sinx2ncosx2nsin2x=2ncosxsinx2ncosx2nsinx==2ntan(x2n)tan(x)Ω=limx0xtan(x)limntan(x/2n)x/2n=1

Commented by aleks041103 last updated on 26/Sep/21

There is an even easier method  tan(2x)=((2tan(x))/(1−tan^2 (x)))⇒1−tan^2 x=2((tan(x))/(tan(2x)))  ⇒Π_(k=1) ^n (1−tan^2 (x/2^k ))=2^n Π_(k=1) ^n ((tan((x/2^k )))/(tan((x/2^(k−1) ))))  telescopic sum:  ⇒Π_(k=1) ^n (1−tan^2 (x/2^k ))=((2^n tan(2^(−n) x))/(tan(x)))  ...  ⇒Ω=1

Thereisaneveneasiermethodtan(2x)=2tan(x)1tan2(x)1tan2x=2tan(x)tan(2x)nk=1(1tan2x2k)=2nnk=1tan(x2k)tan(x2k1)telescopicsum:nk=1(1tan2x2k)=2ntan(2nx)tan(x)...Ω=1

Commented by mathdanisur last updated on 26/Sep/21

Very nice Ser, thank you

VeryniceSer,thankyou

Terms of Service

Privacy Policy

Contact: info@tinkutara.com